2019
DOI: 10.1038/s41598-019-45542-z
|View full text |Cite
|
Sign up to set email alerts
|

Boiling Histotripsy-induced Partial Mechanical Ablation Modulates Tumour Microenvironment by Promoting Immunogenic Cell Death of Cancers

Abstract: Boiling histotripsy is a promising non-invasive High-Intensity Focused Ultrasound (HIFU) technique that employs HIFU mechanical effects to fractionate solid tumours without causing any significant thermal damage. It has been suggested that boiling histotripsy may induce a strong immune response due to the absence of denatured antigenic protein at the HIFU focus. The underlying immunological mechanisms of this technique are, however, poorly understood. In this study, we demonstrated the feasibility of using boi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 48 publications
4
56
0
Order By: Relevance
“…For thermal ablation, continuous wave insonation was applied at 3.1 MPa peak negative pressure (PNP), whereas for mechanical ablation a 16.9 MPa PNP was applied and the duty cycle was www.nature.com/scientificreports/ minimized such that any temperature increase was less than 2 °C. The resulting studies provide a starting point for the comparison of regimes; however, in the future, comparisons to the histotripsy protocols used in [56][57][58][59] must also be made directly with the dedicated lower frequency equipment required for those studies. A disadvantage of such equipment (limiting a comparative study of thermal and mechanical mechanisms) is the larger insonified volume (relative to mouse tumors) and the incompatibility with MR guidance.…”
Section: Discussionmentioning
confidence: 99%
“…For thermal ablation, continuous wave insonation was applied at 3.1 MPa peak negative pressure (PNP), whereas for mechanical ablation a 16.9 MPa PNP was applied and the duty cycle was www.nature.com/scientificreports/ minimized such that any temperature increase was less than 2 °C. The resulting studies provide a starting point for the comparison of regimes; however, in the future, comparisons to the histotripsy protocols used in [56][57][58][59] must also be made directly with the dedicated lower frequency equipment required for those studies. A disadvantage of such equipment (limiting a comparative study of thermal and mechanical mechanisms) is the larger insonified volume (relative to mouse tumors) and the incompatibility with MR guidance.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of this study was to understand the ability of HT40 to reprogram the immunologically cold melanoma tumor such that it becomes more receptive to ICI therapy. HT has been utilized to debulk tumor tissue, release damage associated molecular patterns (DAMPs), and improve immune sensitization in various tumor models 24 , 27 , 36 , 56 . We and others have also shown that local αCD40 therapy activates APCs and improves the functional status of TILs in melanoma 21 , 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Boiling HT is a non-invasive mechanical homogenization technology that rapidly generates tumor antigen depots with sharp boundaries in solid cancers. Since HT achieves heating to 100 ºC by using millisecond-long pulses with lower pulse repetition frequency (PRF) 34 , it avoids denaturation of tumor antigens in the focal regions 36 . Thus, its combination with αCD40 can hypothetically improve tumor immune environment, and immunotherapeutic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear stresses produced around an oscillating boiling vapor bubble and emissions of shockwaves and jetting resulting from a cavitation cluster can contribute to forming a BH lesion. [11,13] In contrast to HIFU thermal ablation, since BH treatment is not greatly affected by heat perfusion via blood flow, BH can produce a sharper transition zone between untreated and treated regions with a transition distance of less than a cell length. During HIFU thermal ablation exposure, for example, normal healthy tissue surrounding the HIFU focus can be thermally ablated due to thermal diffusion effect.…”
Section: Introductionmentioning
confidence: 99%